Study on the Transverse Vibration Characteristics of Phenine Nanotubes - Zhuoqun Zheng; Han Li; Lifeng Wang; Xu Xu; Eric Li (Nanomaterials)
Phenine nanotubes are tubular molecular structures with periodic hexatomic vacancies. The holes formed by these vacancies have a significant impact on their electrical, mechanical, and other properties. In this paper, the transverse vibration characteristics of phenine nanotubes (PNTs) are investigated by molecular dynamics (MD) simulation and continuum mechanics. A geometrically equivalent beam model is established for describing the geometric characteristics of holes. The effective static mechanical parameters of PNTs used in the proposed model are calibrated by MD simulations. The first four-order natural frequencies of PNTs are predicted by MD simulations and geometrically equivalent beam models. The results indicate that the geometrically equivalent beam model performs well in describing the transverse vibration characteristics of PNTs. Furthermore, the applicability ranges of geometrically equivalent beam models are discussed. This study offers valuable insights into the transverse vibration characteristics of porous nanostructure, which would be beneficial for the design of nanoscale mechanical resonators.